2018
DOI: 10.3389/fphy.2018.00012
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Realism of White Matter Numerical Phantoms: A Step toward a Better Understanding of the Influence of Structural Disorders in Diffusion MRI

Abstract: White matter is composed of irregularly packed axons leading to a structural disorder in the extra-axonal space. Diffusion MRI experiments using oscillating gradient spin echo sequences have shown that the diffusivity transverse to axons in this extra-axonal space is dependent on the frequency of the employed sequence. In this study, we observe the same frequency-dependence using 3D simulations of the diffusion process in disordered media. We design a novel white matter numerical phantom generation algorithm w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…This decrease of the ICVF is an effect of the presence of dispersion and deformation of the fibre bundles. However, even in the lowest resolution, the intra-axonal volume fraction achieved was over 48%, which is considerably higher than the icvf (of 20%) of a previously presented framework for generating realistic numerical phantoms for crossing fascicles [20]. By optimizing the penalization term of the strands' curvature in our framework, we expect to be able to achieve even higher packing densities-closer to the expected ones from the brain's white matter tissue.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This decrease of the ICVF is an effect of the presence of dispersion and deformation of the fibre bundles. However, even in the lowest resolution, the intra-axonal volume fraction achieved was over 48%, which is considerably higher than the icvf (of 20%) of a previously presented framework for generating realistic numerical phantoms for crossing fascicles [20]. By optimizing the penalization term of the strands' curvature in our framework, we expect to be able to achieve even higher packing densities-closer to the expected ones from the brain's white matter tissue.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, the intracellular compartment is usually idealised as a collection of parallel hollow cylinders with constant radii or radii sampled from a distribution estimated from histological data [38,17,2,21,2]. Recent studies have suggested that such simplification cannot capture the complexity of the axonal structures of white matter, and thus its diffusion characteristics [31,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dispersion can occur not only in regions of fiber crossing, fiber kissing, but also in regions traditionally expected to be unidirectional such as the corpus callosum [33]. However, 3D models are hard to construct, not only because of the lack of 3D EM data (that could represent a ground truth), but also because of the complexity of 3D axon packing [34]. Also, it could be the case that the 2D axon shapes, used in our realistic WM modeling, are elongated due to being obtained from cutting through axons that were not perpendicular to the surface.…”
Section: Model Parameters Dictionarymentioning
confidence: 99%
“…The most common approach to this is the packing of fibres into densely packed configurations (Close et al, 2009;Ginsburger et al, 2019Ginsburger et al, , 2018Rafael-Patino et al, 2018).…”
Section: Introductionmentioning
confidence: 99%